IMPLEMENTASI MATA KULIAH PENDIDIKAN AGAMA ISLAM DENGAN MENGGUNAKAN ELEARNING - Untung Joko Basuki (JURNAL GAUNG INFORMATIKA, 2015)
As a basic course, the process of teaching subjects Religious Education in college must follow the development of technology. The development of technology that iscurrently widely used is the use of information and communication technology (ICT), especially elearning. By using elearning, the learning process in addition to using the classroom, the material is also uploaded by using elearning facilities. The process of uploading notonly lecture material but also the process of collecting tasks also use elearning facilities. The effectiveness of the use of elearning is felt both by teaching and students.Facilities managed by the Institute of Science & Technology AKPRIND can be accessed at kampus.akprind.ac.id Elearning at IST AKPRIND was developed using the open source Chamilo application and the socialization and training process has been done for the teachersand is expected to elearning the learning process can be further improved.